(untitled) (World Economics and Finance Bulletin, 2024)
The article notes the importance of analyzing the financial condition of an organization in increasing the efficiency of its financial and economic activities, and studies the elements of financial activity, tasks, functions, and the order of stages in analyzing the financial condition of an organization.